The impact of constant effort harvesting on the dynamics of a discrete-time contest competition model - Al-Sharawi, Ziyad (2017)
In this paper, we study a general discrete–time model representing the dynamics of a contest competition species with constant effort exploitation. In particular, we consider the difference equation xn+1 = xnf(xn−k) − hxn where h > 0, k ∈ {0, 1}, and the density dependent function f satisfies certain conditions that are typical of a contest competition. The harvesting parameter h is considered as the main parameter and its effect on the general dynamics of the model is investigated. In the absence of delay in the recruitment (k = 0), we show the effect of h on the stability, the maximum sustainable yield, the persistence of solutions and how the intraspecific competition change from contest to scramble competition. When the delay in recruitment is one (k = 1), we show that a Neimark–Sacker bifurcation occurs, and the obtained invariant curve is supercritical. Furthermore, we give a characterization of the persistent set.